On the social and emotional lives of gifted children understanding and guiding their development - Cross, Tracy L., 1958- (Prufrock Press, 2011)
"Raising happy, successful children is a goal of every parent of gifted children. In On the Social and Emotional Lives of Gifted Children, the nation's leading authority on the psychology of gifted children offers advice and encouragement for both parents and teachers. In a thoughtful, conversational style, the author offers an in-depth look at the complex social and emotional issues faced by gifted children. This revised and updated fourth edition of the popular text contains more than 10 new chapters, featuring contributions by scholars on gifted children's development from across the nation. On the Social and Emotional Lives of Gifted Children tackles important and timely issues dealing with the social and emotional needs of today's gifted children, including who gifted children are and what giftedness means; how parents, teachers, and counselors can guide gifted children; the issues facing gifted students in the 21st century such as technology and terrorism; and how the education of gifted children can adapt for the future. This concise, sensitive look at gifted children and their social and emotional world offers unique insights for both teachers and parents who support these special children."
Keywords: talentované děti -- psychologické aspekty; talentovaní žáci; pedagogika nadaných; gifted children -- psychological aspects; gifted pupils; gifted education; kolektivní monografie; elektronické knihy; collective monographs; electronic books